Di-O-demethylcurcumin protects SK-N-SH cells against mitochondrial and endoplasmic reticulum-mediated apoptotic cell death induced by Aβ25-35. (January 2015) - Pinkaew, Decha; Changtam, Chatchawan; Tocharus, Chainarong; Thummayot, Sarinthorn; Suksamrarn, Apichart; Tocharus, Jiraporn
Highlights: Di- O -demethylcurcumin improves SK-N-SH cells viability induced by Aβ25-35 . Di- O -demethylcurcumin modulates anti-apoptosis in SK-N-SH cells induced by Aβ25-35 . Di- O -demethylcurcumin exerts neuroprotective effect against Aβ25-35 -treatment. Abstract: Alzheimer's disease (AD) is a neurodegenerative and progressive disorder. The hallmark of pathological AD is amyloid plaque which is the accumulation of amyloid β (Aβ) in extracellular neuronal cells and neurofibrillary tangles (NFT) in neuronal cells, which lead to neurotoxicity via reactive oxygen species (ROS) generation related apoptosis. Loss of synapses and synaptic damage are the best correlates of cognitive decline in AD. Neuronal cell death is the main cause of brain dysfunction and cognitive impairment. Aβ activates neuronal death via endoplasmic reticulum (ER) stress and mitochondria apoptosis pathway. This study investigated the underlying mechanisms and effects of di- O -demethylcurcumin in preventing Aβ-induced apoptosis. Pretreatment with di- O -demethylcurcumin for 2 h, which was followed by Aβ25-35 (10 µM) in human neuroblastoma SK-N-SH cells improved cell viability by using MTS assay and decreased neuronal cell apoptosis. Pretreatment with di- O -demethylcurcumin attenuated the number of nuclear condensations and number of apoptotic cells in Aβ25-35 -induced group in a concentration-dependent manner by using transmission electron microscope (TEM) and flow cytometry, respectively. Di- O -demethylcurcumin also increased the ratio of Bcl-XL /Bax protein, and reduced intracellular ROS level, cytochrome c protein expression, cleaved caspase-9 protein expression, and cleaved caspase-3 protein expression. Additionally, di- O -demethylcurcumin treatment also reduced the expression of ER stress protein markers, including protein kinase RNA like endoplasmic reticulum kinase (PERK) phosphorylation, eukaryotic translation initiation factor 2 alpha (eIF2α) phosphorylation, inositol-requiring enzyme 1 (IRE1) phosphorylation, X-box-binding protein-1 (XBP-1), activating transcription factor (ATF6), C/EBP homologous protein (CHOP), and cleaved caspase-12 protein. CHOP and cleaved caspase-12 protein are the key mediators of apoptosis. Our data suggest that di- O -demethylcurcumin is a candidate protectant against neuronal death through its suppression of the apoptosis mediated by mitochondrial death and ER stress pathway.